Estimating the potential cost of a high dose immune tolerance induction (ITI) therapy relative to the cost of a combined therapy of a low dose ITI therapy with bypassing agent prophylaxis. Issue 5 (22nd June 2017) - Kenet, G.; Oladapo, A.; Epstein, J.D.; Thompson, C.; Novack, A.; Nugent, D. J.
Abstract : Introduction: The International Immune Tolerance Study (I‐ITI) demonstrated comparable success rates between low (FVIII 50 IU/kg/TIW) and high dose (FVIII 200 IU/kg/day) regimens. While costlier, the high dose ITI regimen achieved shorter time‐to‐treatment success with fewer bleeding episodes compared to the low dose ITI regimen. Adding bypassing agent prophylaxis (BAP) to a low dose ITI regimen may reduce bleeding while still being less costly than high dose ITI. Aim and Methods: An economic model was developed to compare high dose ITI to low dose ITI with BAP. All model inputs were derived from clinical trials. The I‐ITI study indicated a median time to negative inhibitor titre of 4.6 and 9.2 months and average number of bleeds/patient of 4.2 and 9.9 for the high and low dose regimens respectively. Based on the BAP trials, aPCC (85 U/kg/TIW) and rFVIIa (90 μg/kg/day) achieved a 62% and 45% reduction in bleeding frequency respectively. Cost analysis was from a US third party payer perspective and limited to drug costs. One‐way, two‐way and probabilistic sensitivity analyses were performed. Results: Costs of low dose ITI with aPCC prophylaxis until negative inhibitor titre is achieved was 24.0% less compared to high dose ITI. Low dose ITI with rFVIIa prophylaxis cost 46.5% more compared to high dose ITI. Model results were robust in the majority of the sensitivity analyses. Conclusion: A low dose ITI regimen with aPCC prophylaxis may be cost saving compared to a high dose ITI regimen with the potential to reduce morbidity by lowering the risk for breakthrough bleeds.